2007
DOI: 10.1103/physreve.75.020301
|View full text |Cite
|
Sign up to set email alerts
|

Critical and noncritical jamming of frictional grains

Abstract: We probe the nature of the jamming transition of frictional granular media by studying their vibrational properties as a function of the applied pressure p and friction coefficient . The density of vibrational states exhibits a crossover from a plateau at frequencies տ * ͑p , ͒ to a linear growth for Շ * ͑p , ͒. We show that * is proportional to ⌬z, the excess number of contacts per grain relative to the minimally allowed, isostatic value. For zero and infinitely large friction, typical packings at the jamming… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
203
4
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(238 citation statements)
references
References 19 publications
25
203
4
6
Order By: Relevance
“…One should not be surprised to observe a finite z 0 below jamming: when the vibration is turned off, the structure is quenched abruptly from a vibrational state where the averaged number of contact need not be zero. The sublinear increase of z 0 with packing fraction is compatible with the one obtained in simulations of frictional particles [17,38]. The initial pressure P 0 also increases above jamming from a small residual value below jamming, again inherited from the vibrational state [see Fig.…”
supporting
confidence: 72%
“…One should not be surprised to observe a finite z 0 below jamming: when the vibration is turned off, the structure is quenched abruptly from a vibrational state where the averaged number of contact need not be zero. The sublinear increase of z 0 with packing fraction is compatible with the one obtained in simulations of frictional particles [17,38]. The initial pressure P 0 also increases above jamming from a small residual value below jamming, again inherited from the vibrational state [see Fig.…”
supporting
confidence: 72%
“…In simulations of frictional systems, it is indeed indeed found that packings at the jamming threshold with different values of Z and density φ can be made, by varying in particular the quench rate; moreover, there is a clear trend for the average contact number Z to approach the lower lower limit d + 1 -the isostatic value in the presence of friction -in the limit µ → ∞ [7,82]. In line with this, one finds that if one studies the linear vibration-rotation modes of these packings, the density of states only develops a plateau in this large friction limit [81]. However, it was later discovered that the situation is more subtle.…”
Section: Packings Of Frictional Spheresmentioning
confidence: 55%
“…In the presence of static friction, therefore, the properties of a packing are very history dependent, as the tangential forces are not only dependent on the configuration, but also on how the configuration was made -see e.g. [78][79][80][81].…”
Section: Packings Of Frictional Spheresmentioning
confidence: 99%
“…consistently appears in computer experiments with shear loading near jamming transition [4][5][6][7][8][9] and can be supported by some analytical arguments [7]. The theories relate faster decrease of the elastic shear modulus with pressure in comparison with the bulk modulus to an additional relaxation of the applied shear stress through a non-affine motion of the beads, which does not influence importantly bulk modulus [4][5][6][7].…”
Section: Quadratic Approximation Of Nonlinear Acoustics For An Unconsmentioning
confidence: 65%
“…In particular, behavior of granular media near the jamming transition at zero pressure, where with increasing pressure the emergence of the solid-like elasticity appears, still contains many puzzles [4][5][6][7][8][9]. In addition, the low-pressure region near the phase transition to the solid-like state in a granular material is extremely difficult to access experimentally.…”
Section: Introductionmentioning
confidence: 99%